Evaluation of long-term safety, tolerability, and behavioral outcomes with adjunctive rufinamide in pediatric patients (≥1 to <4 years old) with Lennox-Gastaut syndrome: Final results from randomized study 303. (January 2019) - Arzimanoglou, Alexis; Ferreira, Jose; Satlin, Andrew; Olhaye, Omar; Kumar, Dinesh; Dhadda, Shobha; Bibbiani, Francesco
Abstract: Objective: Evaluate the long-term safety, tolerability, and behavioral effects of adjunctive rufinamide in pediatric patients (≥1 to <4 years old) with inadequately controlled seizures associated with Lennox-Gastaut syndrome (LGS). Methods: Study 303 (ClinicalTrials.gov identifierNCT01405053 ) was a multicenter, randomized, open-label, Phase III trial. Patients were randomized (2:1) to oral suspension rufinamide (≤45 mg/kg/day) or any other investigator-chosen antiepileptic drug (AED) for a 2-year treatment period. Primary safety/tolerability assessments included monitoring of treatment-emergent adverse events (TEAEs) and serious TEAEs. Behavioral effects were assessed via the Child Behavior Checklist (CBCL) using the Total Problems score and change from baseline in CBCL Total Problems score. CBCL subscores were also evaluated. Results: The Safety Analysis Set included 37 patients (rufinamide: n = 25; any other AED: n = 12). TEAE incidence was similar between the rufinamide (88.0%) and any-other-AED groups (83.3%); serious TEAE incidence was also similar between treatment groups (40.0% and 41.7%, respectively). Between treatment groups, the difference in the least squares mean CBCL Total Problems score across time was not significant ( p = 0.7083), behavior outcomes were similar across all endpoints, and there were no consistent trends in CBCL subscores. Significance: Long-term (2 years) adjunctive rufinamide was well tolerated in pediatric patients with LGS. Behavioral outcomes were comparable between the rufinamide and any-other-AED groups, however the small sample size and difficulties assessing behavior in this population should be noted. The challenges of this study raise the issue of revising how studies in very young children with rare and complex epilepsies are performed. Highlights: Lennox-Gastaut syndrome (LGS) has a heterogeneous etiology. Study 303 assessed adjunctive rufinamide in LGS patients aged ≥1 to <4 years. Two years' treatment with adjunctive rufinamide was well tolerated. Behavioral effects were comparable with rufinamide vs other antiepileptic drugs. Rufinamide may be a viable treatment for patients ≥1 to <4 years old with LGS.